Subjective Perceptions of Preservice Teachers' Professional Competence in the Context of Geographical Excursions - Lindau, Anne-Kathrin (Journal of Geography Education, 2021)
The subjective perception of professional knowledge is an important component in the development of professional competence already during teacher training. In this context, complex teaching and learning formats form a significant role, as they contribute to the professionalisation of future teachers by mastering the demands made of them and their subjective perception. Using the example of a geographical excursion within the framework of university teaching education in geography, the handling of complex challenges is analysed against the background of the subjective perception of professional knowledge within a study module. The results show that the subjective perception of the dimensions of professional knowledge change during the planning, implementation and evaluation of a self-organised excursion and that individual resource and development areas for professionalisation are derived.
Keywords: Professional action competence, professional knowledge, subjective perception, pre-service teacher, geography, excursion